The Effect of Ownership Structure and Audit Quality on Firm Performance - Dramani Angsoyiri (Garuda Prestasi Nusantara Consulting, 2021)
The study examined the effect of ownership structure and audit quality on firm performance of listed companies in Ghana. The research employed a quantitative research approach; secondary data was extracted from various annual reports and financial statements of the selected companies. The target population was all 42 listed companies on the Ghana Stock Exchange. The sample size was 20 companies selected from all industries. The study period was 2013-2018 resulted in 160 firm-yearly empirical observations. The study used return on asset (ROA) and return on equity (ROE) as the performance measure. Ownership structure was measured using managerial ownership and institutional ownership, audit quality was also measured with the auditor’s reputation, audit committee size and audit committee independence. The control variables used were board size and firm size. The researcher found a weak positive correlation between institutional and managerial ownership and firm performance. Moreover, there was a positive effect of audit quality on firm performance. It implies that the engagement of the services of the Big 4 audit firms has an incremental effect on firm performance. Audit committee size posited a positive effect on firm performance whereas audit committee independence was seen to harm firm performance. Similarly, board independence showed a positive effect on ROE and a negative effect on ROA. Board size, however, indicated a positive effect on firm performance. The researcher recommended the pressing need of diversifying shareholdings in firms as a sweetener to attract more skills and expertise among shareholders that can be tapped to enhance the performance of firms. However, managers should be protected from unnecessary shareholding meddling.